Perlindungan Tahanan Pada Kamp-Kamp Penahanan Amerika Serikat - Soraya, Yasmine MS (UI Scholars Hub, 2021)
On May, 19th 2006, UN Anti-Torture Committee delivered a report that suggest a closing of the Guantanamo detention camp. The government of the United States of America then look an action by establishing the Law on Interrogation. The law stipulates several principles such as interrogation method and trial on terrorism that somehow legalizes the use of any means of force in such process. Another possibility that is stipulated in the Law is a conviction even the evidence is not visible. Tje protection of prisoner in the United States of America’s detention camp is regulated by both International law and national law. The tortures in such camps that was conducted to obtain a certain information have violated human rights that have been govern by international law and United States of Amarica’s national law itself.